« Notre solidarité n’est pas une solidarité de salon » : le lesbianisme politique décolonial des Lesbiennes of Color (LOCs) face aux nationalismes sexuels - Blase A. Provitola (Genre, Sexualité et Société)
American queer theory, including queer of color critique, is often evoked in France to analyze the growing inclusion of certain so-called “progressive” sexual values within the nation. Yet more and more activists, as well as some academics, are calling for greater attention to local genealogies of decolonial and anti-heteronormative resistance in the struggle against sexual nationalisms. This article responds to this call by examining the writings and organizing strategies of the contemporary collective known as the Lesbiennes of Color (LOCs) since its creation in 2009. The LOCs’ activism provides strategies of resistance to sexual nationalisms, helps to expand queer of color critique beyond anglophone sources, and combats Western epistemic imperialism while highlighting the importance of political lesbianism.